If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -25 = 12x + 85 Reorder the terms: -25 + 14x = 12x + 85 Reorder the terms: -25 + 14x = 85 + 12x Solving -25 + 14x = 85 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -25 + 14x + -12x = 85 + 12x + -12x Combine like terms: 14x + -12x = 2x -25 + 2x = 85 + 12x + -12x Combine like terms: 12x + -12x = 0 -25 + 2x = 85 + 0 -25 + 2x = 85 Add '25' to each side of the equation. -25 + 25 + 2x = 85 + 25 Combine like terms: -25 + 25 = 0 0 + 2x = 85 + 25 2x = 85 + 25 Combine like terms: 85 + 25 = 110 2x = 110 Divide each side by '2'. x = 55 Simplifying x = 55
| 5x^2+6x+5y^2-y-9=0 | | -7=-(n-10) | | 10y=4y+7+5y | | 5(1+k)=-6(3-2k)+2 | | 10y=4y+5y | | 8v^2-74v-60=0 | | 2x^3+3x^2=5x | | -6(x+1)=4x-9+2(2x-5) | | 9v^2-62v-80=0 | | o=10y-40 | | 9n-2=7n-50 | | -9(x-1)+4x=-4 | | 6+2(5u-2)=-3(2u-3)+2u | | 2p+7p-4=50 | | -3(4n+8)+8=-14-12n | | 16+2=14 | | 7x+3(x-10)=90 | | 5(2x-10)=40 | | 3x=200 | | 7.3(5.1-x)+2.73=2x+2.8 | | 3x+12=10x+40 | | 3x^4-2x^3+6x^2=0 | | j-3=-3 | | 6x+2(3x-16)=40 | | 12-4m=0 | | -6+(m+8)=-11 | | 7m+38=4(m+5) | | 2x^3-24x+13=0 | | 4x+3(2x-17)=49 | | 5x^5+x+5=0 | | 6x^2+14x+30=0 | | 4x-2x+8=-10 |